Влияние трансформирующего фактора роста-β, эпидермального фактора роста и инсулина на пролиферацию клеток в среде с полужидким агаром - Стойка, Р.С.; Сушельницкий, С.И.; Кусень, С.И. (Биополимеры и клетка, 1989)
Обнаружены существенные различия между мышиными фибробластами линий NІН-3Т3 и Swiss-3Т3 по пролиферации клеток в среде с полужидким агаром после воздействия на них различных сочетаний трансформирующего фактора роста-β, эпидермального фактора роста и инсулина. Виявлено суттєві відмінності між мишачими фібробластами ліній NІН-3Т3 і Swiss-3Т3 за проліферацією клітин у середовищі з напіврідким агаром після впливу на них різних сполучень трансформуючого фактора росту-β, епідермального фактора росту та інсуліну. The transforming growth factor-f5 (TGF-J3), which was isolated and purified by the authors from pig thrombocytes, epidermal growth factor (EGF) and insulin are studied for their effect on cellular proliferation in semisolid culture medium with 0.33 % agar. The lines N1H-3T3 and Swiss-373 of the mouse fibroblasts and rat NRK-49F cells are tested. It was shown that TGF-fi (0.05-50.0 ng/ml) stimulates multiplication of the cells of the mentioned lines only in the presence of EGF (2.5 ng/ml). Synergism in the action of two growth factors is detected when NIH-3T3 and NRK-49F cells are used but it is less expressed in the case of Swiss-3T3 cells. Insulin (1 |ig/ml) intensifies the growth stimulating activity of EGF plus TGF-|3 mixture for Swiss-373 cells bult it inhibits this activity when NIH-373 cells are tested. Thus, the same combination of growth factors can inhibit the expression of phenotypic transformation in one type of cells and can intensify it in other cells being closely related by their origin.